Thermal and Mass Stratification Effects on Unsteady Flow Past an Accelerated Infinite Vertical Plate with Variable Temperature and Exponential Mass Diffusion in Porous Medium - Kumar, Himangshu; Deka, Rudra Kanta (East European Journal of Physics, 2023)
This study looks at how thermal and mass stratification affect the unsteady flow past an infinitely fast-moving vertical plate when the temperature is changing and there is exponential mass diffusion in a porous medium. By applying the Laplace transformation method, we determine the solutions to the equations that govern the system for the case of unitary Prandtl and Schmidt numbers. Graphical representations of the concentration, temperature, and velocity profiles, as well as the Nusselt Number, Sherwood number, and the Skin friction are provided to facilitate discussion of the cause of the different variables. To see the effects of thermal and mass stratification on the fluid flow, we compare the classical solution (Fluid with out stratification) with the primary solution (Fluid with the stratification) by using graph. The combined effects of the two stratification lead to a quicker approach to steady states. The outcomes can be helpful for heat exchange design and other engineering applications.